2014
DOI: 10.1055/s-0034-1374616
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Sensitive LC-MS/MS Assay for the Determination of Saxagliptin and its Active Metabolite 5-hydroxy Saxagliptin in Human Plasma and its Application to a Pharmacokinetic Study

Abstract: The authors proposed a simple, rapid and sensitive liquid chromatography-tandem mass spectrometric (LC-MS/MS) assay method for the simultaneous determination of saxagliptin and its active metabolite 5-hydroxy saxagliptin in human plasma. The developed method was fully validated as per the US FDA guidelines. The method utilized stable labeled isotopes saxagliptin-15 N d2 (IS1) and 5-hydroxy saxagliptin-15 N-d2 (IS2) as internal standards for the quantification of saxagliptin and 5-hydroxy saxagliptin, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In addition, adequate retention of the analytes was a major challenge in the simultaneous analysis of MET, SAXA and 5‐OH SAXA because of their varying polarities. MET, being highly polar, has been shown to have poor retention on conventional C 18 reversed‐phase columns (Michel et al, ; Nielsen et al, ; Zhang et al, ), while SAXA and 5‐OH SAXA can be adequately retained on these columns within acceptable run times (Batta et al, ; Gao et al, ; Xu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, adequate retention of the analytes was a major challenge in the simultaneous analysis of MET, SAXA and 5‐OH SAXA because of their varying polarities. MET, being highly polar, has been shown to have poor retention on conventional C 18 reversed‐phase columns (Michel et al, ; Nielsen et al, ; Zhang et al, ), while SAXA and 5‐OH SAXA can be adequately retained on these columns within acceptable run times (Batta et al, ; Gao et al, ; Xu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…There are other reports in which MET has been determined with some DPP‐4 inhibitors, namely, vildagliptin (Pontarolo et al, ) and sitagliptin (Bonde et al, ; Reddy, Ahmed, Ahmad, Mukhopadhyay, & Thangam, ; Swales, Gallagher, Denn, & Peter, ; Scherf‐Clavel & Hogger, ). Likewise, a number of bioanalytical methods are presented for the determination of SAXA (Fura et al, ; Gao, Yuan, Lu, & Yao, ) and with its active metabolite 5‐OH SAXA (Batta et al, ; Xu et al, ) in different biological fluids. However, there are only two reports based on LC–MS/MS which were specifically intended to study the bioequivalence of SAXA/MET extended release (XR) (Gummesson et al, ) and immediate release (IR) (Upreti et al, ) FDC tablet formulation with corresponding monotherapy of these drugs in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Batta et al (2015) reported an interesting method for the measurement of both saxagliptin and 5-hydroxysaxagliptin in human plasma. Because of the sensitivity issues, a positive ionization mode was preferred over that of negative ionization mode as it gave enhanced signal and permitted multiple reaction monitoring (MRM) detection with better selectivity (Batta et al, 2015). The choice of volatile buffer (i.e.…”
Section: Bioanalysis Of Other Dpp4 Inhibitorsmentioning
confidence: 99%
“…ammonium acetate) was crucial as part of the mobile phase as it provided the ionization potential and enabled better sensitivity with symmetrical peak shapes of both saxagliptin and 5-hydroxysaxagliptin. Lastly, the method employed solid-phase extraction (SPE), which not only enabled higher recoveries for both analytes but also gave an alternative option for sample extraction outside of protein precipitation and LLE (Batta et al, 2015).…”
Section: Bioanalysis Of Other Dpp4 Inhibitorsmentioning
confidence: 99%
“…HPLC-MS/MS method has been extensively used to investigate pharmacokinetic profiles of new drug owing to its high specificity, sensitivity and rapid analysis speed, especially for multiple reaction monitoring (MRM) scan mode (Batta et al, 2015;Diao et al, 2013;Shah, Shah, Sanyal, & Shrivastav, 2016;Wang, Jiang, Hu, & Zhao, 2017;Wang, Zheng, Wang, Hu, & Jiang, 2017). Therefore, in view of the previous method, a specific, sensitive and rapid method based on HPLC-MS/MS with MRM scan mode was developed and fully validated to quantify imigliptin, its five metabolites, and alogliptin in human plasma and urine.…”
mentioning
confidence: 99%